Hubungan Lama Kerja dan Aktivitas Kerja Monoton dengan Kelelahan Kerja pada Pedagang Ikan Pasar Angso Duo - Rd. Halim; Budi Aswin (Jurnal Riset Hesti Medan, 2022)
The causes of work fatigue consist of several conditions, including long working conditions and monotonous work activities. Research objective: This study aims to analyze the relationship between length of work and monotonous work activities with the incidence of work fatigue in the Angso Duo fish market traders in Jambi. The study used a cross-sectional design. The population in this study were all fish traders at the Angso Duo market who had worked for at least 10 years, amounting to 90 traders. The research sample amounted to 90 people who were taken using a total sampling technique. Collecting data by observation, and using a questionnaire. Data processing was carried out univariate and bivariate using chi-square test at 95% confidence interval. The results: The results showed that length of work (p=0.003) and monotonous work activities (p=0.001) were associated with the incidence of work fatigue in fish traders. The conclusion: there is a relationship between length of work and monotonous work activities with the incidence of work fatigue at the Angso Duo fish market in Jambi city.